An Analysis of Differentiated Learning in English Subject of Phase D in Merdeka Curriculum - Fadila Amalia Berinal; Absharini Kardena; Reflinda Reflinda; Genta Sakti (International Journal of Education, Information Technology, and Others, 2026)
This research aimed to analyze the implementation of differentiated learning in the English subject of Phase D in Merdeka Curriculum. The study used a qualitative case study approach involving three English teachers as research informants. The data were collected through classroom observations and interviews to explore teachers’ experiences in applying differentiated learning in the teaching and learning process. The findings revealed that teachers implemented differentiated learning through four main aspects: content, process, product, and learning environment. In content differentiation, teachers adjusted learning materials according to students’ readiness and interests by using simple language and starting from basic concepts. In process differentiation, teachers applied various teaching strategies such as group discussions and the use of visual media to accommodate students’ learning styles. In product differentiation, students were given different options to present their learning outcomes based on their abilities and creativity. Meanwhile, the learning environment was designed to be interactive and collaborative to support students’ participation. However, teachers also faced several challenges, including students’ different English proficiency levels, limited learning resources, and difficulties in meeting all students’ needs simultaneously. Overall, differentiated learning helped create a more student-centered learning environment, although further support and resources are needed to optimize its implementation.